Myxedema Coma: A Rare Case of Shock Post-Pericardial Window Procedure. Issue 16 (December 2022) - Asllanaj, Blerina; Olson, Mark; McWhorter, Yi
The clinical features of severe hypothyroidism vary in presentation, ranging from subclinical symptoms to multiorgan failure referred to as myxedema coma. The cornerstone treatments of myxedema coma include aggressive thyroid hormone replacement combined with excellent supportive care in the intensive care unit. We report a rare case of a 56-year-old female with history of hypothyroidism treated with levothyroxine, who developed myxedema coma post-pericardial window surgery for a large pericardial effusion. She was supported with substantial doses of vasopressors and inotropes for shock. In addition, she was initiated on lung-protection ventilation for acute respiratory distress syndrome. After the diagnosis of myxedema coma was made, she was started on intravenous levothyroxine and hydrocortisone with great sustained clinical response. This case illustrated myxedema coma as an unusual cause of shock in post-operative patients with past medical history of hypothyroidism.